Innen vor Außen? Eine Schätzung der Innenentwicklung in nordrhein-westfälischen Gemeinden, 1979 bis 2011 - Eichhorn, Sebastian; Siedentop, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Strengthening inner urban development is a guiding principle of Germany’s sustainability policy and the key to achieving the 30-hectare target. To date, however, it is hardly possible to determine retrospectively the share of building construction activity realized as inner and outer urban development. On the one hand, there is the genuine fuzziness of the inner urban area (Innenbereich) as a spatial construct, and on the other hand, there is the lack of available small-scale data on building construction activity. Against this background, this paper presents for the first time a methodological approach to determine and evaluate the relevance of inner urban development for large areas and over longer periods of time for Germany. The method is applied for the federal state of North Rhine-Westphalia and the housing construction activity from 1979 to 2011. The result shows a positive trend, indicating that cities and municipalities have succeeded in realizing more housing as inner urban development over time. At the same time, significant differences between urban and rural areas are apparent. A central conclusion is therefore to support smaller municipalities in their efforts for more inner urban development.